Predominance of synovial sensory nerve fibers in arthrofibrosis following total knee arthroplasty compared to osteoarthritis of the knee. Issue 1 (December 2016) - Koeck, Franz; Schmitt, Miriam; Baier, Clemens; Stangl, Hubert; Beckmann, Johannes; Grifka, Joachim; Straub, Rainer
Abstract Background So far, there exists no golden standard for the treatment of arthrofibrosis (AF) following total knee arthroplasty (TKA). Although pain is a hallmark of AF, nociceptive nerve fibers have never been investigated in affected joint tissue. Methods A total of 24 patients with osteoarthritis (OA) of the knee (n = 12) and post-TKA AF of the knee (n = 12) were included. Along evaluation of typical clinical signs and symptoms by using the Knee Society Clinical Rating System (KSS), the Knee Injury and Osteoarthritis Outcome Score (KOOS), and the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC index), the innervation of joint tissue was studied by semiquantitative immunofluorescence of nerve fibers. Results Patients with AF compared to OA had a lower KSS and lower KOOS. In all compartments (anterior, medial, and lateral recesses), the density of synovial sympathetic nerve fibers was significantly higher in OA compared to AF, which was also true for the density of sensory nerve fibers in the medial and lateral recesses. In synovial tissue of the anterior recess of patients with AF compared to OA, the density of nociceptive sensory nerve fibers was significantly higher relative to sympathetic nerve fibers. This was similarly observed in the neighboring infrapatellar fat pad of the knee. Conclusions Similar as in many painful musculoskeletal diseases, this study indicates that patients with arthrofibrosis of the knee after TKA demonstrate a preponderance of profibrotic sensory nerve fibers over antifibrotic sympathetic nerve fibers. This could serve as a starting point for AF therapy with specific antifibrotic pain medication or regional anesthetic techniques.